Implementation of the Qardh Agreement on the Financial Technology Lending Platform in the Development of Small and Medium Enterprises (SME) in Indonesia - Firdaus, Muhammad Irkham; Tifani, M. Akhlis Azamuddin; Putri, Sri Firda Rahmi Aliya; Zulfikri, Zulfikri (University of Darusssalam Gontor, 2022)
Financial technology is a new financial innovation that has an important role in the development of the national economy. The convenience offered is the main attraction among the people. besides that it also has a very high impact on the development of Small and Medium Enterprises (SME). However, the system applied is the same as the conventional financial system, such as the interest system on online loans. Although innovative and helpful, the interest system applied is the same as a loan from a loan shark, where the interest given is very burdensome. So in this study, we discuss the implementation of qardh contracts on the financial technology lending platform, and how it affects the development of SME. This type of research is library research, which is research conducted by collecting data from various literature books, journals, website writings, magazines, laws, fatwas, or from various writings. The approach used in this research is qualitative, where the research procedure uses descriptive data in the form of written words. The researcher will explain the terms and elements that must be met in implementing the qardh contract on the peer to peer lending platform. The result is, the implementation of qardh contracts on financial technology lending platforms should avoid the various elements namely riba, gharar, maysir, tadlis, dharar, zhulm, and haram. If in practice all these elements are avoided, it will facilitate all actors of SME. Where the perpetrator will not be stuck in huge debt because of interest, and avoid ambiguity and fraud that will be to the detriment of one party. In addition, the existence of the qardh contract based financial technology loan platform will make it easier for SME actors to obtain loans or capital to develop their SME.Financial technology (fintech) merupakan inovasi keuangan baru yang memiliki peran penting dalam pembangunan perekonomian nasional. Kenyamanan yang ditawarkan menjadi daya tarik tersendiri bagi masyarakat. selain itu juga berdampak sangat tinggi terhadap perkembangan Usaha Kecil Menengah (UKM). Namun sistem yang diterapkan sama dengan sistem keuangan konvensional, seperti sistem bunga pinjaman online. Meski inovatif dan membantu, sistem bunga yang diterapkan sama seperti pinjaman dari rentenir, di mana bunga yang diberikan sangat memberatkan. Maka dalam penelitian ini, kami membahas implementasi akad qardh pada platform fintech lending, dan bagaimana pengaruhnya terhadap perkembangan UKM. Jenis penelitian ini adalah penelitian kepustakaan, yaitu penelitian yang dilakukan dengan mengumpulkan data dari berbagai literatur buku, jurnal, tulisan website, majalah, undang-undang, fatwa, atau dari berbagai tulisan. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif, dimana prosedur penelitian menggunakan data deskriptif berupa kata-kata tertulis. Peneliti akan menjelaskan syarat dan unsur yang harus dipenuhi dalam pelaksanaan akad qardh pada platform peer to peer lending. Hasilnya, pelaksanaan akad qardh pada platform fintech lending harus menghindari berbagai unsur yakni riba, gharar, maysir, tadlis, dharar, zhulm, dan haram. Jika dalam praktiknya semua elemen tersebut dihindari, maka akan memudahkan semua pelaku UKM. Di mana pelaku tidak akan terjerat hutang yang besar karena bunga, serta terhindar dari kerancuan dan penipuan yang akan merugikan salah satu pihak. Selain itu, dengan adanya platform pinjaman fintech berbasis akad qardh akan semakin memudahkan para pelaku UKM untuk mendapatkan pinjaman atau modal untuk mengembangkan UKM-nya.